A model for the allocation and utilisation of academic staff resources - Griew, Stephen (Canadian Journal of Higher Education, 1980)
It is argued that since an institution's recurrent income is so critically dependent on its total full-time equivalent enrolment, resource allocation should be based on measures of the contributions of individual teaching units to the institution's total full-time enrolment. A model is presented that permits the estimation of such contributions. The parameters generated by this model provide a basis for judgements concerning the efficiency of academic staff utilisation, the equitable deployment of staff in matrix organisations, the utilisation of staff in complex settings such as the professional school, and the assess- ment of spare, re-allocable teaching capacity. It is argued that the model assists an institution in facing up to the constraints imposed by its staff utilisation policies and, further, that it generates information of a kind that facilitates rational planning and decision-making in the allocation and utilisation of scarce teaching resources.